Spinal injuries in adolescent athletes - Powell, L. D.
Because of their age and involvement in vigorous activities and sports, adolescents risk injury to the spine (back bone). Certain types of sport activities increase the risk of injury, especially to the lower back. However, these athletes can take steps to prevent many types of spinal injuries.